Steps to Ensure a Successful Implementation of Occupational Health and Safety Interventions at an Organizational Level - Herrera-Sánchez, Isabel M.; León-Pérez, José M.; León-Rubio, José M. (Frontiers in Psychology, 2017)
There is increasing meta-analytic evidence that addresses the positive impact of evidence-based occupational health and safety interventions on employee health and well-being. However, such evidence is less clear when interventions are approached at an organizational level and are aimed at changing organizational policies and processes. Given that occupational health and safety interventions are usually tailored to specific organizational contexts, generalizing and transferring such interventions to other organizations is a complex endeavor. In response, several authors have argued that an evaluation of the implementation process is crucial for assessing the intervention’s effectiveness and for understanding how and why the intervention has been (un)successful. Thus, this paper focuses on the implementation process and attempts to move this field forward by identifying the main factors that contribute toward ensuring a greater success of occupational health and safety interventions conducted at the organizational level. In doing so, we propose some steps that can guide a successful implementation. These implementation steps are illustrated using examples of evidence-based best practices reported in the literature that have described and systematically evaluated the implementation process behind their interventions during the last decade.